Teaching about home visits to university students - Fernanda Ribeiro Borges; Carolina Costa Valcanti Avelino; Livia Cristina Scalon da Costa; Daniela Santos Lourenço; Maurício Durval de Sá; Sueli Leiko Takamatsu Goyatá (Universidade Federal do Ceará, 2017)
To identify the scientific evidence available in the literature on the teaching strategies used in the home visit. Methods: it is an integrative literature review in the Nursing Database, Scientific Electronic Library Online, Latin American and Caribbean Literature in Health Sciences, and Cumulative Index to Nursing & Allied Health Literature. Results: six articles with evidence strength level VI were included. Different strategies and teaching methods related to the home visit activity were found, such as socio-drama, active methodologies and curricular practices in the health services network. Experiencing social reality was a potentiality, and there was lack of planning of the visit as weaknesses found by the students. Conclusion: the main teaching strategy for university students in the health area is the early insertion for the direct monitoring of families through home visits.